Prispevek k poznavanju flore Ribniške doline (Dolenjska, Slovenija) - Bačič, Tinka (Natura Sloveniae, 2000)
During the Youth Research Camp Dolenja vas '98 in the begining of July 1998, some floristic investigations were carried out in the south-western part of the Dolenjska region. The research was based on the mapping of vascular plant in two quadrants of MTB grid, covering the Ribnica valley and its surroundings. The article discusses the results of this research and presents some of the most interesting recorded species: Leonurus cardiaca, Daclylorhizamaculata ssp. transsilvanica, Vulpia ciliata, Senecio paludosus, Senecio aquaticus, Sisyrinchium bermudiana and Tanacetum narthenium.
Keywords: Dolenjska; Ecosystem; flora; Lower Carniola; Plants; Ribnica